The Great Gatsby and its Allegorical Meaning (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2020)
This article seeks to analyze the novel The Great Gatsby (1925) as a narrative and iconographic representation of the American Dream. The first part of the article highlights the concept of allegory presented by Walter Benjamin in describing the engraving Angelus Novus (1920) in which he associates iconography and narrative. The concept will be tied to the novel as a key to reading and interpretation. In the novel, the American Dream associated with the desire for material goods is reconnected to a pastoral aura through the character Gatsby, idealized male projection. This aspect is going to be highlighted in the second part of the article. The conclusion resumes the resizing of the American Dream as a manifest allegory in atemporal space. Space, in the novel, is constructed as a system in which the belonging of characters to places determines their relations of power.